9(1+3n)=9(1-12n)

Simple and best practice solution for 9(1+3n)=9(1-12n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(1+3n)=9(1-12n) equation:


Simplifying
9(1 + 3n) = 9(1 + -12n)
(1 * 9 + 3n * 9) = 9(1 + -12n)
(9 + 27n) = 9(1 + -12n)
9 + 27n = (1 * 9 + -12n * 9)
9 + 27n = (9 + -108n)

Add '-9' to each side of the equation.
9 + -9 + 27n = 9 + -9 + -108n

Combine like terms: 9 + -9 = 0
0 + 27n = 9 + -9 + -108n
27n = 9 + -9 + -108n

Combine like terms: 9 + -9 = 0
27n = 0 + -108n
27n = -108n

Solving
27n = -108n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '108n' to each side of the equation.
27n + 108n = -108n + 108n

Combine like terms: 27n + 108n = 135n
135n = -108n + 108n

Combine like terms: -108n + 108n = 0
135n = 0

Divide each side by '135'.
n = 0

Simplifying
n = 0

See similar equations:

| 16+15r+19r= | | 7x+11=10x-19 | | k=21 | | 2xsquared=4x+126 | | x-5/x+3/x=2/3 | | 10+4+3m+7m= | | -8(2x-4)=-13-x | | F=13fgh | | 7x+26=-3x+4(x+2) | | 14+5x=13+6x | | 6g-18g= | | 5r^2+20r+18=3 | | 18=-6(3x+15) | | 8x^3-4x^2-12x=0 | | 4/n+9=2/7 | | K-6k= | | 6x-x=5 | | 5x+5(-7x+16)=160 | | a^2-20a+44=0 | | 8(5x-9)= | | 20-5x=4+3x | | 7(-5r-8)-r=-236 | | 6+7x=180 | | Y=2.5x-40 | | 22m+6n+(4m-8)=26m+6n+8 | | 35=9(6a-7) | | 3y+y^2-10= | | -130.3005=3.3(5.05r-0.6) | | m^2-6m-51=0 | | -(-8x-3)-x=4x+6(-5+x) | | 2x+75=3x | | -2a-3b= |

Equations solver categories